Activity of PD-1 blockade with nivolumab among patients with recurrent atypical/anaplastic meningioma: phase II trial results. Issue 1 (20th May 2021) - Bi, Wenya Linda; Nayak, Lakshmi; Meredith, David M; Driver, Joseph; Du, Ziming; Hoffman, Samantha; Li, Yvonne; Lee, Eudocia Quant; Beroukhim, Rameen; Rinne, Mikael; McFaline-Figueroa, Ricardo; Chukwueke, Ugonma; et al.
Abstract: Background: Programmed death ligand 1 (PD-L1) contributes to tumor immunosuppression and is upregulated in aggressive meningiomas. We performed a phase II study of nivolumab, a programmed death 1 (PD-1) blocking antibody among patients with grade ≥2 meningioma that recurred after surgery and radiation therapy. Methods: Twenty-five patients received nivolumab (240 mg biweekly) until progression, voluntary withdrawal, unacceptable toxicity, or death. Tumor mutational burden (TMB) and quantification of tumor-infiltrating lymphocytes (TIL) were evaluated as potential immunocorrelative biomarkers. Change in neurologic function was prospectively assessed using the Neurologic Assessment in Neuro-Oncology (NANO) scale. Results: Enrolled patients had multiple recurrences including ≥3 prior surgeries and ≥2 prior courses of radiation in 60% and 72%, respectively. Nivolumab was well tolerated with no unexpected adverse events. Six-month progression-free survival (PFS-6) rate was 42.4% (95% CI: 22.8, 60.7) and the median OS was 30.9 months (95% CI: 17.6, NA). One patient achieved radiographic response (ongoing at 4.5 years). TMB was >10/Mb in 2 of 15 profiled tumors (13.3%). Baseline TIL density was low but increased posttreatment in 3 patients including both patients with elevated TMB. Most patients who achieved PFS-6 maintained neurologic function prior to progression as assessed by NANO. Conclusion: Nivolumab was well tolerated but failed to improve PFS-6, although a subset of patients appeared to derive benefit. Low levels of TMB and TIL density were typically observed. NANO assessment of neurologic function contributed to outcome assessment. Future studies may consider rationally designed combinatorial regimens.